An improved biofunction of Titanium for keratoprosthesis by hydroxyapatite-coating. (March 2014) - Dong, Ying; Yang, Jingxin; Wang, Liqiang; Ma, Xiao; Huang, Yifei; Qiu, Zhiye; Cui, Fuzhai
Titanium framework keratoprosthesis has been commonly used in the severe corneal blindness, but the tissue melting occurred frequently around titanium. Since hydroxyapatite has been approved to possess a good tissue integration characteristic, nanostructured hydroxyapatite was coated on the surface of titanium through the aerosol deposition method. In this study, nanostructured hydroxyapatite coating was characterized by X-ray diffraction, scanning electron microscopy, atomic force microscopy, and auger electronic spectrometer. Biological evaluations were performed with rabbit cornea fibroblast in vitro and an animal model in vivo. The outcomes showed the coating had a grain-like surface topography and a good atomic mixed area with substrate. The rabbit cornea fibroblasts appeared a good adhesion on the surface of nanostructured hydroxyapatite in vitro. In the animal model, nanostructured hydroxyapatite-titanium implants were stably retained in the rabbit cornea, and by contrast, the corneal stroma became thinner anterior to the implants in the control. Therefore, our findings proved that nanostructured hydroxyapatite-titanium could not only provide an improved bond for substrate but also enhance the tissue integration with implants in host. As a promising material, nanostructured hydroxyapatite-titanium–based keratoprosthesis prepared by the aerosol deposition method could be utilized for the corneal blindness treatment.